Intersemiotic Relations between Verbal and Visual Elements in Engineering Students’ Final Project Reports: A Lesson of Academic Writing Courses - Febryanto, Mohammad; Zewitra, Zewitra; Khorina, Mulyati; Bakhti, Krisna Yudha (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
The integration of verbal and visual resources is critical for explaining technical information in engineering academic writing. While earlier research has looked extensively into intersemiotic relationships in textbooks, classroom materials, and scientific texts, limited attention has been paid on engineering students' final project reports. This study investigates the intersemiotic relationships between verbal and visual elements in final project reports written by engineering students. The study used a qualitative content analysis design and examined 20 final project reports from four engineering programs: Road and Bridge Design Engineering, Mechanical Design and Construction Engineering, Refrigeration and Air Conditioning Engineering, and Power Plant Engineering. Halliday's logico-semantic linkages and Martinec and Salway's intersemiotic framework served as foundations for the investigation. The results revealed two intersemiotic categories: elaboration (90.08%) and enhancement (9.92%), with no instances of extension observed. Clarification was the most frequent subtype of elaboration (74.09%), followed by exposition (9.18%) and exemplification (6.82%). Within enhancement, manner accounted for 81.25% of the occurrences, while spatial relations accounted for 18.75%. The high level of clarification suggests that engineering students rely largely on visual resources to clarify and reinforce technical concepts, procedures, and systems that are difficult to describe verbally. These findings indicate that engineering academic writing is essentially multimodal, with visual resources serving as primary meaning-making tools rather than supplemental illustrations. The study contributes to intersemiotic research by expanding its application to authentic engineering academic writing.